The Contribution of Community Health Education to Sustainable Control of the Neglected Zoonotic Diseases - Butala, Caitlin; Fyfe, Jenna; Welburn, Susan Christina (Frontiers in Public Health, 2021)
Effective and sustainable control of the Neglected Zoonoses (NZDs) demands a One Health approach. NZDs largely impact on individuals in low- and middle-income countries, disproportionally affecting resource poor communities with poor access to veterinary and human health services and to clean water and which are intrinsically dependent on animals for their livlihoods. Many NZDs in humans can be treated, but treatment is often complex and expensive. Similarly, while tools for prevention of transmission may exist, they exist are complex and expensive to adopt at the scale required to be effective. The cost of intervention for NZDs is high when compared to the public health benefits alone but costs are easily outweighed by full cross sector analysis and when monetary and non-monetary benefits to all stakeholders are considered. Education is a key tool, often overlooked in favor of more complex solutions for the control of NZDs. Successful education programs have been targeted to children of school age for Taenia solium in Kenya, schistosomiasis in Nigeria, and soil transmitted helminths in China. A Snakes and Ladders board game, designed to teach children about schistosomiasis and encourage compliance with mass deworming programs, deployed in Nigerian schools, showed a 67% increase in knowledge of praziquantel and 65% of children who had previously rejected treatment requested the drug. For soil transmitted helminths in China, presentation of health information in cartoon format rather than in poster format, showed post-assessment knowledge to be 90% higher. With the rise in affordable smart-phone technology, internet access and airtime in communities in low- and middle- income countries e-education is an increasingly attractive proposition as an intervention tool for the NZDs. The Vicious Worm, a computer based educational health tool that has been designed around the prevention of Taenia Solium has shown remarkable efficacy in affected communities in which it has been deployed with participants applying the principles learned in their communities. This review explores the successes and benefits of education as a control tool for the NZDs.